Anticancer effect of paroxetine and amitriptyline on HT29 and A549 cell lines. (March 2023) - Motafeghi, Farzaneh; Shahsavari, Romina; Mortazavi, Parham; Shokrzadeh, Mohammad
Abstract: Introduction: Paroxetine is functionally classified as a selective serotonin reuptake inhibitor. Paroxetine can induce mitochondria-dependent apoptosis through the ROS-MAPK pathway.Amitriptyline is a tricyclic antidepressant. This drug induces the expression of p53, thereby activating caspase-3. Amitriptyline has also been studied as a potential candidate for inducing oxidative stress and cytotoxicity in cancer cells, which may be more effective than other chemotherapy drugs. This study aims to to investigate the anticancer effects of paroxetine and amitriptyline and their combination treatment on HT29 and A549 cell lines for the first time. Methods: In order to investigate the anticancer effect of two drugs, paroxetine and amitriptyline, on inhibiting the growth of A549 and HT29 cancer cells, oxidative stress factors and LDH enzyme and apoptosis tests were performed. Results: Two drugs, amitriptyline and paroxetine alone, inhibited the growth of cancer cells in such a way that the inhibitory effect of the cells increased with the increase in the dose of the drug. In the simultaneous exposure of these two drugs, the inhibitory effect was much greater than the effect of single drug exposure. Also, these two drugs have caused LDH leakage and induction of apoptosis. Conclusion: According to the results of the study, it was found that these two drugs have the necessary ability to inhibit the growth of cancer cells by inducing apoptosis and LDH leakage and inducing oxidative stress. Highlights: Paroxetine and amitriptyline induced mitochondrial dysfunction. Paroxetine and amitriptyline release LDH from A549 and HT-29 cell lines. Paroxetine and amitriptyline induction of apoptosis in cancer cells.